Concerning the Relationship between Different Types of Identification and Evidentiary Value of Expert Findings - N. P. Maylis (Теория и практика судебной экспертизы, 2017)
The article discusses the issues of identification in terms of its types, the relationship between them, the relevancy of expert findings and their evidentiary value.